Abuse to the elderly people residing south of Mexico City - Lopez Fernandez, Rosa (2019)
The main objective of this study was to detect if there was abuse in elderly people living in the south of Mexico City, in addition to know the type of abuse, sex and age where it appears most frequently. The hypothesis was that there was abuse in older people who lived in this area. A descriptive and correlational study was carried out, with a quantitative approach, a non-experimental, cross-sectional design was made. 200 elderly people participated, chosen in a non-probabilistic way and for convenience, the Development and psychometric properties scale of the Geriatric Mistreatment Scale was applied (Giraldo, 2013). To analyze the data, the statistical program SPSS was used. The results showed that, in the south of Mexico City, there is abuse to the elderly, with a higher percentage of psychological abuse. Neither age nor sex were related to the type or frequency of abuse.